Halal fashion: Strategi pemasaran dengan marketing mix 9P - Hapsari, Mega Tunjung (Nur Science Institute, 2022)
There have been many marketing mix strategies that have been carried out in the business world, but this research is different because it combines sharia marketing with the 9P marketing mix method, which includes product strategy, price, promotion, place, people, process, physical evidence, payment, and product packaging, as well as supporting factors, barriers, and solutions to Ebi Parfum Jombang's efforts to increase product sales. The approach used is descriptive qualitative with primary and secondary data. Interactive model data analysis with validation using triangulation. The research results are: 1) Sharia marketing through the 9P marketing mix implemented by Ebi Parfum paying attention to sharia values, namely fathanah, shiddiq, tabligh, and amanah; using halal ingredients and always maintaining product quality. Of the nine elements of the marketing mix, there are two dominant elements in the success of sharia marketing, namely product and price strategies. 2) The supporting factors for sharia marketing through the 9P marketing mix in the Ebi Parfum business are halal and quality ingredients, wide product distribution, competitive selling prices, product differentiation, and innovation. Meanwhile, the inhibiting factors are the limited stock of bottles, large capital, many competitors, and vulnerability to leaks for long-distance shipments.